Collaborative D2D communication in relay networks with energy harvesting - Li, Qiang; Ren, Pinyi (China communications, 2022)
Although the collaborative transmission of cellular network and device-to-device (D2D) pairs can improve spectrum utilization, it also results in the matual interference, which may be fatal for low-energy D2D pairs. Based on this, we propose in this paper a collaborative D2D transmission scheme with erergy harvesting (CDTEH) in a relay network, where D2D pairs are allowed to access the spectrum of relay network to accomplish their own transmission. In particular, the relay with energy harvesting is arranged to not only expand cellular transmission range but also assist D2D and cellular users to eliminate the mutual interference. To evaluate the performance, rate-energy (R-E) region is introduced. Based on the model, a data rate maximization problem of D2D pair is formulated, subject to a transmission demand of the cellular user and the optimal solution is acquired. Finally, numerical results are provided to validate the proposed scheme improves the data rate of D2D pair ensuring the cellular transmission requirement.